Review of exercise-induced asthma - Storms, W. W. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: The purpose of this manuscript is to review the recent literature on exercise-induced asthma (EIA) and summarize the pathogenesis, diagnosis, and treatment of this condition. METHOD: A review of the English language medical literature was performed to obtain articles on EIA. RESULTS: The pathophysiology of EIA is not fully understood, but there are two theories: 1) the hyperosmolar theory and 2) the airway rewarming theory. In addition, there have been data to show that airway inflammation is present in some elite athletes, especially in cold weather sports. The diagnosis of EIA is usually straightforward in most patients, but a number of patients may have atypical symptoms and may be more difficult to diagnose. They may well need exercise testing or eucapnic voluntary ventilation testing. Most people respond to treatment with an inhaled beta agonist and or cromolyn before exercise, but some patients will also need other medications, including daily medications such as inhaled steroids. When treatment does not control the problem, then further diagnostic evaluation should be done to rule out conditions other than EIA, such as vocal cord dysfunction or cardiac or pulmonary problems. CONCLUSIONS: EIA is a condition that may occur in schoolchildren in gym class and also in Olympic athletes. The diagnosis and treatment is usually fairly straightforward, but at times it may be challenging. However, all patients should be followed to make sure that the correct diagnosis is made and to make sure that treatment is effective.